Low-Cost Real-Time Gas Monitoring Using a Laser Plasma Induced by a Third Harmonic Q-Switched Nd-YAG Laser - Abdulmadjid, Syahrun Nur; Kurniawan, Koo Hendrik; Lie, Tjung Jie; Lee, Yong Inn; Kitazima, Iwao; Kagawa, Kiichiro (ITB Journal Publisher, LPPM ITB, 2005)
A gas plasma induced by a third harmonic Nd-YAG laser with relatively low pulsed energy (about 10 mJ) has favorable characteristics for gas analysis due to its low background characteristics, nevertheless a high power fundamental Nd-YAG laser (100-200 mJ) is widely used for laser gas breakdown spectroscopy. The air plasma can be used as a low-cost real-time gas monitoring system such that it can be used to detect the local absolute humidity, while a helium plasma can be used for gas analysis with a high level of sensitivity. A new technique using a helium plasma to improve laser ablation emission spectroscopy is proposed. Namely, the third harmonic Nd-YAG laser is focused at a point located some distance from the target in the 1-atm helium surrounding gas. By using this method, the ablated vapor from the target is excited through helium atoms in a metastable state in the helium plasma.